ChemInform Abstract: Deep Eutectic Solvent Catalyzed Friedel—Crafts Alkylation of Electron‐Rich Arenes with Aldehydes. Issue 50 (December 2015) - Wang, Ailing; Xing, Pengfei; Zheng, Xueliang; Cao, Hongyu; Yang, Guang; Zheng, Xuefang
Abstract: Triarylmethanes and diarylalkanes are synthesized by the title method under mild reaction conditions in high yields.